Association between unilateral functional ankle instability, limited ankle dorsiflexion range of motion and low back pain - Mahmoud Diab Abdelhaleem; Mariam Omran Grase; Sobhy Mahmoud Aly; Ehab Ali Abdallah (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.